Congenital Zika syndrome: geographical access to the health care network - Danielle Amaral de Freitas; Mayumi Duarte Wakimoto; Reinaldo Souza-Santos (Revista de Saúde Pública, 2025)
ABSTRACT OBJECTIVES To analyze the geographic access of children with congenital Zika syndrome (CZS), residing in the city of Rio de Janeiro between 2015 and 2017, to rehabilitation services. METHODS Ecological study, based on spatial analysis. Commute maps were constructed using QGis 3.36.3 and the distances, time and cost between rehabilitation services and the homes of children with CZS, in the city of Rio de Janeiro, reported between 2015 and 2017 in the Registry System of Public Health Events. RESULTS 47 children were identified, 6 died. Among the 41 survivors, 17 were followed up in primary and secondary health care (PHC and SHC), 10 only in PHC, 7 only in SHC, and 7 had no follow-up record. CZS cases were more frequent in the north and west zones of the city. 143 trajectories followed by the 36 children between home and a rehabilitation service were identified; 147 commutes, followed 1 to 106 times; the majority destined for 3 units (n = 17 – 47.0%). The largest number of trajectories and commutes were among residents in the north and west zones of the city, poorer regions, with greater distances, cost, and time spent traveling between home and the health unit. CONCLUSIONS The variation in trajectories, the number of recorded commutes, and the number of units included in the trajectories suggest the complexity of the children’s clinical condition, from basic care in PHC to procedures with greater technological density in specialized care.